Analisis Sistem Informasi Akuntasi (SIA) Dalam Meningkatkatkan Kinerja Bagian Perencanaan Dan Keuangan Pada Kantor Walikota Medan - Seri Mulyani; Rahmat Daim Harahap (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research aims to determine and understand the role of the Accounting Information System (AIS) in improving performance in the Planning and Finance section of the Medan Mayor's Office. The method used in this research is a qualitative descriptive method. The data collection techniques used in this research are through interviews, observations, and documentation. The results of this research show that the Accounting Information System (AIS) plays a very important role in helping Planning and Finance employees in preparing financial reports. Employees just need to input data into the system, then the process of classification, summarization until finally a financial report is formed is carried out automatically by the system.